2016
DOI: 10.1038/cgt.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic cell death by oncolytic herpes simplex virus type 1 in squamous cell carcinoma cells

Abstract: Molecules essential for the induction of immunogenic cell death (ICD) are called damage-associated molecular patterns (DAMPs). The effects of oncolytic herpes simplex virus type 1 (HSV-1) on the production of DAMPs were examined in squamous cell carcinoma (SCC) cells. The cytopathic effects of HSV-1 RH2 were observed in mouse SCCVII cells infected at a high multiplicity of infection (MOI), and the amounts of viable cells were decreased. After being infected with RH2, ATP and high mobility group box 1 (HMGB1) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 47 publications
3
66
0
Order By: Relevance
“…Previous reports have suggested that cells infected with HSV-1 can release byproducts that kill uninfected neighboring cells [22, 23]. We wondered if such a paracrine signal might cause uninfected cells to be more sensitive to alisertib cytotoxicity, contributing to the synergy.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports have suggested that cells infected with HSV-1 can release byproducts that kill uninfected neighboring cells [22, 23]. We wondered if such a paracrine signal might cause uninfected cells to be more sensitive to alisertib cytotoxicity, contributing to the synergy.…”
Section: Resultsmentioning
confidence: 94%
“…Stanziale and colleagues noted that virus infection increased apoptosis in uninfected cells and limited virus spread, which was reversed with an inhibitor of apoptosis [22]. Takasu et al noted oHSV infection induced a so-called immunogenic cell death with secretion of damage associated molecular patterns ATP and HMGB1, and that intratumoral injection of supernatants from infected cells slowed tumor growth [23]. Although the exact nature of molecules that mediate the bystander effect are not known, it is possible this phenomenon will sensitize cells not only to alisertib but also to other targeted or cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of other OVs may also induce bona fide ICD, as they indeed serve to prime/induce adaptive antitumor immunity in vivo . The list is quite long and includes oncolytic adenovirus (46), influenza virus (47), HSV (25, 48, 49), measles virus (MeV) (50), NDV (51), VSV (5), and Sendai virus (52). However, we wish to emphasize that significantly more investigations will be required to validate such conjecture.…”
Section: Current Strategies In Oncolytic Immunotherapymentioning
confidence: 99%
“…Furthermore, cell death with immunogenic potential, i.e. , immunogenic cell death, was also demonstrated in RH2-infected SCC cells [47].…”
Section: Antitumor Immunitymentioning
confidence: 90%